Geoheritage 5. Geoscience Heritage in New Brunswick - Miller, Randall F. (Geoscience Canada, 2009)
Geoheritage encompasses a broad range of topics, from the preservation of geological sites, to maintenance of archival and specimen collections, gathering and dissemination of data, legislation, and geotourism. New Brunswick has a long history of geological investigations that have considerably advanced our understanding of a complicated geological past spanning one billion years. Although the province contains a number of classic geological sites, and many of the first geological explorations in the country were conducted here, only two of more than 1100 historic sites in the province are based on geohistory. Fortunately, geoheritage resources are readily available in New Brunswick, and many of the early geosites are still accessible. Improving geoheritage in New Brunswick is, in part, the responsibility of members of the local geo-science community, which knows it best. Existing heritage systems, such as New Brunswick’s Register of Historic Places and the national Historic Places Initiative, provide the means to ensure that geoheritage becomes part of society’s collective heritage awareness. SOMMAIRE La notion de patrimoine géologique recouvre une gamme variée de sujets d’intérêt, allant de la préservation de sites géologiques, à l’entretien de collections d’archives et d’échantillons, à la collecte et à la dissémination de données, à la règlementation en cette matière, et au géotourisme. La longue tradition de recherches géologique du Nouveau-Brunswick ont permis d’améliorer substantiellement nos connaissances d’une l’histoire géologique compliquée s’étendant sur un milliard d’années. Bien que la province compte de nombreux sites géologiques classiques, dont de nombreux sites des premières recherches géologiques au pays, seuls deux de ces sites sur plus de 1 100 sites à valeur historique de la province sont de nature géo-historique. Heureusement, au Nouveau-Brunswick les ressources géologiques patrimoniales sont facilement accessibles, et nombre des premiers sites géologiques le sont encore. L’amélioration de la situation du patrimoine géologique au Nouveau-Brunswick est, pour une part, du ressort des membres de la communauté géoscientifique locale, étant des experts en sciences de la Terre. Les organismes patrimoniaux existants, comme le Répertoire des lieux patrimoniaux, et l’Initiative des endroits historiques du Nouveau-Brunswick sont des moyens de faire des questions de patrimoine géologique des sujets de préoccupation de la société.